Building and maintaining a volunteer community: experiences of an image archive - Graf, Nicole (Frontiers in Earth Science, 2024)
The ETH-Library's Image Archive has been using the knowledge of volunteers for over 15 years to identify photographs (aerial images, documentary and scientific photographs, press photography, etc.) correct and improve image metadata or georeference images. The first big challenge in starting so-called crowdsourcing projects is how to find people who might be enthusiastic about such a project. The second big challenge is how to maintain a community and keep it going over a longer period. A variety of experiences, tips as well as do's and don'ts are discussed in the article.Crowdsourcing is a form of collaboration in which tasks are outsourced to an undefined mass of people. These tasks can be in different areas, e. g., knowledge generation, product development or service delivery.